The Impact of CO2 Regeneration Positions on Electrochemical CO2 Reduction - Zhuo Chen; Yuesheng Zhang; Huiying Deng; Yuhang Wang (ChemElectroChem)
Implementing electrochemical CO2 reduction can decarbonize practical chemical and fuel production. However, in a typical CO2 electrolyzer, electrochemical CO2 capture (i.e., CO2 reacts with electrochemically produced OH− to form (bi)carbonates that are subsequently regenerated to CO2 by the H+ flux in the reactor) commences in parallel with its electroreduction. Such a phenomenon is observed in various electrolyzer configurations with different electrolyte compositions. This concept begins with a brief discussion on how CO2 capture occurs in CO2 electrolyzers and focuses on the impact of CO2 regeneration locations, including the anode, the electrolyte, and the ion‐exchange membrane, on CO2 electrolysis performance. It is shown that the key to overcoming the low CO2 utilization and operational lifetime is positioning CO2 regeneration on ion‐exchange membranes. The goal is to highlight the essential role of the ion flow management approach in designing high‐performance CO2 electrolyzers. It would contribute to commercializing CO2 electrolyzers for carbon‐neutral chemical synthesis.